The Concept Of Takhalluq And Character Development Aspect In The Thoughts Of Banjar Scholars On Al-Asma' Al-Husna - Rahmadi Rahmadi; Zulfa Jamalie (Jurnal Ushuluddin, 2024)
This article aims to describe and compare the concepts of takhalluq (emulating the character of Allah) and the aspects of character formation in the thoughts of the Banjarese scholars regarding al-Asma al-Husna, as found in their respective works. To examine the Banjarese ulama’s thoughts, the author utilizes a literature study or library research approach in the form of a descriptive-comparative analysis of the ideas of these prominent figures. This study reveals that the concept of takhalluq holds a significant role within the framework of al-Asma al-Husna, following ma’rifah (true knowledge of Allah). The concept of takhalluq is integral to interpreting the word "ihsha," as found in the popular hadith concerning al-Asma al-Husna. According to the Banjarese ulama, the meaning of ihsha cannot be grasped through memorization alone, as the meaning of ihsha itself has layered depths. These layers of meaning encompass (1) memorization, (2) using it in worship (prayer, part of dhikr, and the practice of wirid), (3) comprehending its meaning to the extent that it engenders a sense of awe towards Allah, and (4) adhering to it and internalizing it, resulting in the development of ma’rifah and the cultivation of noble character (takhalluq) rooted in the best names of Allah. Thus, within the perspective of Banjarese ulama, takhalluq represents the highest level of meaning within ihsha`. In the realm of takhalluq, Banjarese ulama emphasize the need to exhibit behavior and ethics akin to the attributes of Allah, following human capacity and appropriateness. This serves as the central point of agreement among the Banjarese scholars under examination, with variations primarily arising in the technical presentation of the names of Allah and their respective perspectives in expounding al-Asma` al-Husna. These variations encompass theological, Sufi, and ethical dimensions